Effect of oxygen pressure on structure and ionic conductivity of epitaxial Li0.33La0.55TiO3 solid electrolyte thin films produced by pulsed laser deposition. Issue 66 (29th June 2016) - Bharathi, K. Kamala; Tan, H.; Takeuchi, S.; Meshi, L.; Shen, H.; Shin, J.; Takeuchi, I.; Bendersky, L. A.
Abstract : We report on the ionic conductivity of Li0.33 La0.55 TiO3 (LLTO) epitaxial films grown on the (100) and (111) surfaces of single crystal SrTiO3 (STO) substrates at different oxygen partial pressures (from 1.33 to 26.66 Pa). Abstract : We report on the ionic conductivity of Li0.33 La0.55 TiO3 (LLTO) epitaxial films grown on the (100) and (111) surfaces of single crystal SrTiO3 (STO) substrates at different oxygen partial pressures (from 1.33 to 26.66 Pa). The films are intended for use as solid electrolytes for all-solid-state Li-ion batteries, and the epitaxial growth for modeling the electrolyte single crystal properties. The LLTO films overall exhibit formation of the perovskite-based orthorhombic structure with the epitaxial cube-on-cube orientation for both (100)STO and (111)STO substrates. Room temperature ionic conductivity of the LLTO films measured by impedance spectroscopy slightly decreases with the oxygen partial pressure changing from 1.33 to 26.66 Pa and is in the range of 10 −4 to 10 −5 S cm −1 . Complex impedance plots at different temperatures indicate that the conductivity in these epitaxial films is predominantly an intrinsic bulk property and exhibits distribution of relaxation time. Activation energies ( E a ) for all the films were calculated employing the Arrhenius relationship and are between 0.30 eV and 0.40 eV, agreeing well with the reported values of bulk materials. Systematic difference in ionic conductivity between the (100)STO and (111)STO films is understood as being related to the difference in distribution of a "bottleneck" diffusion path. The measured conductivity of LLTO films indicates that these films can be used as a solid electrolyte in all-solid-state batteries.